THE STATE'S RESPONSIBILITY IN THE WELFARE OF PEOPLE AND ECONOMIC RECOVERY IN THE FACE OF COVID-19 FROM THE PERSPECTIVE OF LAW AND HUMAN RIGHTS - Aprita, Serlika; Anisah, Lilies (Universitas Islam Negeri Raden Fatah Palembang, 2021)
The Covid-19 pandemic was taking place in almost all countries around the world. Along with the increasingly vigorous government strategy in tackling the spread of the corona virus that was still endemic until now, the government had started to enforce the Large-Scale Social Restrictions (PSBB) with the signing of Government Regulation (PP) No. 21 of 2020 about PSBB which was considered able to accelerate countermeasures while preventing the spread of corona that was increasingly widespread in Indonesia. The research method used was normative prescriptive. The government put forward the principle of the state as a problem solver. The government minimized the use of region errors as legitimacy to decentralization. The government should facilitated regional best practices in handling the pandemic. Thus, the pandemic can be handled more effectively. The consideration, the region had special needs which were not always accommodated in national policies. The government policy should be able to encourage the birth of regional innovations in handling the pandemic as a form of fulfilling human rights in the field of health. Innovation was useful in getting around the limitations and differences in the context of each region. In principle, decentralization required positive incentives, not penalties. Therefore, incentive-based central policies were more awaited in handling and minimizing the impact of the pandemic.